STAGES OF ORGANIZATION OF ENGLISH LESSONS - Boltaeva, Gulilola (Журнал иностранных языков и лингвистики, 2023)
The thesis provides the structure, sequence, interdependence, and effectiveness of foreign language lessons for students with clear evidence. The results of the research and studies of scientists are given as real-life examples and recommendations, both applicable and unnecessary.